2020
DOI: 10.1016/j.vetmic.2020.108605
|View full text |Cite
|
Sign up to set email alerts
|

Bearing the brunt: Mongolian khulan (Equus hemionus hemionus) are exposed to multiple influenza A strains

Abstract: The majority of influenza A virus strains are hosted in nature by several Anseriformes and Charadriformes birds. A minority of strains have been able to cross species boundaries and establish themselves in novel non-avian hosts. Influenza viruses of horses, donkeys, and mules represent successful cases of avian to mammal influenza virus adaptation. Mongolia has over 3 million domestic horses and is home to two wild equids, the Asiatic wild ass (Equus hemionus hemionus), and Przewalski horse (Equus ferus przewa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…All of the above means that the decrease in reproductive potential during the domestication of new economically valuable species of animals (for example, the Asiatic wild ass Equus hemionus hemionus (Soilemetzidou et al, 2020)) can be compensated either by artificial selection for fertility in addition to the main desired trait or through interbreed crosses. When natural habitats of wild animals are included into economic land rotation by humans, an inbreeding-related diminution of their reproductive potential takes place (up to ex tinction), which can be compensated by subspecies crossings of these animals and by methods of assisted reproductive technology.…”
Section: Resultsmentioning
confidence: 99%
“…All of the above means that the decrease in reproductive potential during the domestication of new economically valuable species of animals (for example, the Asiatic wild ass Equus hemionus hemionus (Soilemetzidou et al, 2020)) can be compensated either by artificial selection for fertility in addition to the main desired trait or through interbreed crosses. When natural habitats of wild animals are included into economic land rotation by humans, an inbreeding-related diminution of their reproductive potential takes place (up to ex tinction), which can be compensated by subspecies crossings of these animals and by methods of assisted reproductive technology.…”
Section: Resultsmentioning
confidence: 99%
“…While cross-reaction with the H7N9 strain was excluded in both cases, antibodies obtained from the horses were assigned as H7N7 using a protein microarray (PA) technique, but when one of the sera was additionally tested via single radial haemolysis assay, it proved to be H7N3 positive. The authors suggested co-circulation of both subtypes, which are of equine and avian origin, respectively [ 51 ]. Antibodies to the H7 protein were also detected in the same animal species in Nigeria [ 52 ], where a haemagglutination inhibition technique using H7N3 antigen was applied.…”
Section: Discussionmentioning
confidence: 99%